Long-term Results of Conservative Therapy of Adolescent Idiopathic Scoliosis Using the Cheneau Brace - Weniger, Carmen Dorothea; Fujak, Albert; Hofner, Benjamin; Fuchs, Markus; Forst, Raimund; Richter, Richard Heinrich (Klinische Pädiatrie, 2019)
Adolescent idiopathic scoliosis is a disease of the growing skeleton. The goal in therapy is to decelerate or to prevent progression of the spinal curve. As part of a retrospective study the patient group of the scoliosis surgery from 1995–2016 was analysed according to the inclusion criteria of the Scoliosis research Society (SRS). 159 of 643 of the patients fullfilled the specific criteria. The assessment of effectiveness was based on the progression of the angle of curvature. If it was ≤5° it was judged positively. The therapy in accordance to Cheneau is a full-time bracing orthosis. Data from 159 patients – 136 fem. (85.5%), 23 male (14.5%) was analysed. The average age at the beginning of treatment was 13.3±1.7 years. The average duration was 3.47±1.2 years. The average Cobb-angle before treatment was 28.39°±9.44°. At the completion is was 27.7°±12.34°. Stabilisation of scoliosis (≤5°) was achieved for 136 of the patients (85.5%). The final follow-up showed a progression of the Cobb angel>5° in 23 cases, of which 19 had to undergo secondary surgery. The length of therapy had a positive influence (p=0.057) on the result. Brace treatment constitutes an effective method of therapy at curvatures between 20–40°. Short duration of therapy correlates with a expressively increased risk towards progression (p=0.057). The Cheneau brace treatment constitutes an effective treatment at curvature angles between 20–40°. The risk of progression can be reduced by a timely and correct identification.
Keywords: long-term results of conservative therapy in scoliosis; Cheneau Brace; adolescent idiopathic scoliosis; long term results concerning SRS criteria